1991
DOI: 10.1159/000217017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Advanced Malignant Melanoma by a Pyrogenic Bacterial Lysate. A Pilot Study

Abstract: Fifteen patients (8 female, 7 male) with advanced melanoma received intravenous injections of a pyrogenic bacterial lysate consisting of streptococci and serratia marcescens. In three cases with skin metas-tases, this kind of treatment resulted in a total and long lasting remission. In another case with inguinal lymphnode metastases, a five month period of stability was achieved. The remaining eleven patients showed further progression of their disease. Side-effects of therapy included fever, nausea, headache,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This study demonstrates that HSP70 protein and mRNA can be induced de novo under fever conditions in human PBMCs. The data were obtained during fever therapy of melanoma patients [16]. The induction of HSP70 is not the unique effect of a special pyrogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrates that HSP70 protein and mRNA can be induced de novo under fever conditions in human PBMCs. The data were obtained during fever therapy of melanoma patients [16]. The induction of HSP70 is not the unique effect of a special pyrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of the heat shock response was tested in patients (Table 1) suffering from metastatic melanoma and undergoing fever therapy. The patients were treated either with lyophilized benzylpenicillin-treated Streptococcus pyrogenes group A (OK-432, Picibanil, Chugai Pharmaceutical Company, Tokyo, Japan) [15] or with an autolysate of Serratia marcescens and streptococci (Vaccineurin, Südmedica, Munich, Germany) [16]. Application was intravenous except for patient 7, who received Picibanil intradermally into the tumour.…”
Section: Patients and Induction Of Fevermentioning
confidence: 99%
“…Due to the frequently observed association of spontaneous regression with febrile infection, experimental treatments with bacterial lysates commenced after the second half of the 19th century and are still being attempted to date [43,52,53]. Kölmel et al [54] found physiological changes in serum parameters measured after intravenous doses of toxins. At the peak temperature increased values for interleukin-1, interleukin-2, interferon-gamma and the tumor necrosis factor, and after 48 h, an increased value for monocytes, natural killer cells, and B and T lymphocytes are found.…”
Section: Discussionmentioning
confidence: 99%
“…34,36,37 Otherwise, MBV was largely safe. 18,19,[38][39][40] Up to 15 different preparations of MBV existed, but not all were potent enough to induce high fever and durable remissions. 30,41 This was particularly the case with the commercial preparations used mostly outside of New York.…”
Section: Reviewmentioning
confidence: 99%